Gender differences in the associations between perceived environment and walking for recreation in Taiwanese adults. Issue 5 (28th May 2017) - Liao, Yung; Lin, Cheng-Yi; Huang, Jing-Huei; Park, Jong-Hwan
ABSTRACT: This study examined gender differences in the associations between perceived environmental factors and walking for recreation in Taiwanese adults. In 2014, a telephone-based, cross-sectional survey targeting Taiwanese adults (20–64 years) was conducted. Data on nine items about environmental perception, time spent in walking for recreation, and socio-demographic variables were obtained from 1, 065 adults using the International Physical Activity Questionnaire-long version and its environmental module. Adults who perceived good aesthetics (adjusted odds ratio [AOR] = 1.74; 95% confidence interval [CI]: 1.36– 2.23) and reported seeing people being active (AOR = 1.58; 95% CI: 1.21– 2.06) were more likely to perform 150 minutes of recreational walking per week. Furthermore, significant interactions regarding walking for recreation were observed between gender and five environmental correlates: access to shops ( p = .046), the presence of sidewalks ( p < .001), access to recreational facilities ( p = .02), seeing people being active ( p = .001), and aesthetics ( p < .001). These five perceived environmental factors were positively associated with recreational walking in women but not in men. Gender is a potential modifier between perceived environment and walking for recreation in adults. Perceived environmental factors appear to be more critical for women in performing health-enhancing levels of recreational walking than they are for men.